ANALISA KELAYAKAN ETANOL KADAR RENDAH SEBAGAI BAHAN BAKAR PADA KOMPOR BERGRAVITASI - Wardi Salim, Ahmad; Mara, Made; Padang, Yesung Allo (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2013)
Low grade alcohol  is energy that can be renewed. when compared to kerosene and LPG, bioethanol stove is non explossive, does not require a large pressure and easy to manufacture.This study to determine the effect of the height and length of  heating coil burner water heating time, preparation time and fuel consumption. The principle of low grade of ethanol stove is used the position of the fuel tank height and speed up the process of  evaporation. Variations used in this study is the length of the heating coil burner that is 55 cm, 75 cm, 95cm, and height is given by 1.5 m, 1.75 m, and 2 m.The results indicate that the use water heating fastest time obtained at 2 m height variation with of 95 cm burner heating coil of 790 seconds. At the time of preparation reduction obtained at the optimal height variation of 1.5 mand lenghth 95 cm of burner heating coils is 328 sekonds. The lowest fuel consumption obtained when using length variation burner heating coil 55 cm and a height of 1.5 m  at 0.132 ml/sec.